2012
DOI: 10.3109/14767058.2012.743521
|View full text |Cite
|
Sign up to set email alerts
|

Role of fetal echocardiography in the evaluation of structure and function of fetal heart in diabetic pregnancies

Abstract: Fetuses of women with well-controlled gestational diabetes lack the diastolic dysfunction that is present in fetuses of women with pre-existing diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 16 publications
4
37
1
Order By: Relevance
“…The M-mode is widely used in fetal 2D echocardiography, especially to assess cardiac arrhythmias; 30 however, it can also be applied to evaluate cardiac function by f-TAPSE and f-VSF. 14,31 The greatest disadvantage of the real-time M-mode is achieving an adequate fetal position and the need for minimal fetal movements and maternal breathing. STIC enables the acquisition and offline analysis of 3D fetal heart volume, with less dependence on the fetal position and experience of the examiner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The M-mode is widely used in fetal 2D echocardiography, especially to assess cardiac arrhythmias; 30 however, it can also be applied to evaluate cardiac function by f-TAPSE and f-VSF. 14,31 The greatest disadvantage of the real-time M-mode is achieving an adequate fetal position and the need for minimal fetal movements and maternal breathing. STIC enables the acquisition and offline analysis of 3D fetal heart volume, with less dependence on the fetal position and experience of the examiner.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Another parameter frequently evaluated using the M-mode is the ventricular shortening fraction (VSF), which is abnormal in fetuses of pregnant women with preexisting diabetes. 14 The evaluation of fetal cardiac function using three-dimensional ultrasonography (3DUS) and spatiotemporal image correlation (STIC), virtual organ computer-aided analysis (VOCAL), and automated volume calculation (SonoAVC) softwares was shown to be reproducible in the evaluation of stroke volume, fraction ejection, and cardiac output in normal fetuses. [15][16][17] STIC M-mode enables the easy acquisition of the plane of four chambers via offline analysis of fetal heart volume.…”
mentioning
confidence: 99%
“…The MPI is calculated using a formula for which the isovolumetric contraction time (ICT) plus isovolumetric relaxation time (IRT) is divided by ejection time (ET) ([ICT + IRT]/ET) . Isovolumetric contraction time (ICT) is related to systolic function, while IRT is related to diastolic function . As the heart rate or ventricular structure or gestational age is less likely to affect the result of equation, the MPI mainly depends on the elapsed times .…”
Section: Functional Evaluationmentioning
confidence: 99%
“…Hypertrophic cardiomyopathy affects the right ventricle and the posterior left ventricular wall, but the septal hypertrophy is more evident because of the large number of insulin receptors in the septum of the heart. 9,19,20 In our study, we observed that only 2 of the 34 fetuses with HCM exhibited alterations in the left ventricular wall, but none of them exhibited alterations in the septum.…”
Section: Discussionmentioning
confidence: 52%
“…[6][7][8] An increase in the ventricular wall thickness may also be involved in the cardiac changes observed in fetuses of mothers with GDM, but septal hypertrophy is more studied because of the higher number of insulin receptors in the septum of the heart. 9 Prenatal HCM is diagnosed through intrauterine two-dimensional echocardiography, and, based on the results, physicians may provide appropriate postnatal care and follow-up for cardiac hypertrophy progression during the gestational period. 10 Some authors claim that fetal echocardiography should be recommended to all pregnant women with GDM.…”
Section: Introductionmentioning
confidence: 99%